Die Gattungen der Familie Aphidiidae und ihre verwandtschaftliche Zuordnung (Hymenoptera: Ichneumonoidea). - Mackauer, Manfred (Contributions to Entomology = Beiträge zur Entomologie, 1961)
In the present paper, the family Aphidiidae (Hymenoptera) is divided into different groups of systematic relationship. The phylogenetic origin of subfamilies, tribes, and genera is discussed. Ephedrinae and Prainae are considered to be "Schwestergruppen" of Aclitinae + Aphidiinae. According to the shape of valvifer II the latter can be divided into two monophyletic groups: Aphidiini (Paralipsina, Lysiphlebina, Aphidiina, Protaphidiina) and Trioxini (Monoctonina, Trioxina). Nomenclatural ActsAclitinae Mackauer, 1961 (Aphidiidae), subfam. n.Ephedrinae Mackauer, 1961 (Aphidiidae), subfam. n.Prainae Mackauer, 1961 (Aphidiidae), subfam. n.Paralipsina Mackauer, 1961 (Aphidiini), subtrib. n.Monoctonina Mackauer, 1961 (Trioxini), subtrib. n.